Light chain myeloma: A brief report from India - Neha Singh; Narendra Agrawal; Radhika Sekhri; Anurag Mehta; Dushyant Kumar; Gayatri Vishwakarma; Rayaz Ahmed; Dinesh Bhurani (Wolters Kluwer Medknow Publications, 2019)
Light chain myeloma (LCM) has a reported worldwide incidence of approximately 15%-20% among all multiple myeloma (MM) patients. Few western studies have shown strong correlation of LCM with anemia, higher International Staging System scores, proclivity to renal failure, elevated lactate dehydrogenase levels, raised serum-free light chain ratio, higher frequency of extramedullary plasmacytomas, and poorer overall survival, attributable probably to lack of differentiation and skeletal destruction. The primary aim of this retrospective observational study was to define the clinical and hematological characteristics as well as prognostic outcome of Indian LCM patients in comparison with the IgG and IgA subtypes. Patients were defined according to the International Myeloma Working Group diagnostic criteria 2016 and staged as per the International Staging System. Out of 104 patients of newly diagnosed MM in which results of serum immunofixation (IFE) were available, 65 were of IgG isotype (62.5%), 15 had IgA (14.4%), and 24 had light chain myelomas (LCMs) (23.1%). It was observed that LCM patients significantly correlated with hypercalcemia and higher serum-free light chain ratios, whereas IgA patients were strongly associated with anemia and lower serum albumin levels. However, no difference was found among the three subgroups in terms of serum lactate dehydrogenase levels, proclivity to renal failure, presence of lytic bone lesions, prognostic scoring, pretransplant chemosensitivity, and progession-free survival (1 year). Thus, it may be concluded that Indian LCM patients have significantly different clinico-hematological profile in comparison with other published studies worldwide. Also, their prognostic outcomes are not worse when compared with patients of other protein isotypes, probably due to standardized treatment regimens applied.